Evolutionary dynamics of the B chromosomes in the fish species Prochilodus lineatus Valenciennes, 1837 of the Paraná River Basin - Penitente, Manolo; Goes, Caio Augusto Gomes [UNESP]; dos Santos, Rodrigo Zeni [UNESP]; Utsunomia, Ricardo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fabio [UNESP] (Pensoft Publishers, 2025)
The fish species Prochilodus lineatus has an interesting B chromosome system, with three morphological types as acrocentric, metacentric, and submetacentric. However, most cytogenetic studies on this species are restricted to the natural population of the Mogi Guaçu River. Given this, the present work aimed to study the structure karyotypic profile as well as the occurrence of supernumeraries in P. lineatus in several localities in the Paraná River basin, where this species is abundant. The results obtained showed a predominantly conserved karyotypic macrostructure and the presence of B chromosomes in all the seven localities studied, with the exception of the Apa River. Additionally, new variants of morphological characteristics were found in the population of the Batalha River (Reginópolis). These results allow us to infer that there is a large occurrence of B chromosomes in this species, with important differences in B chromosome frequency between the populations, especially in acrocentric and submetacentric B variants. Considering the possible origin and evolution of B chromosomes in P. lineatus, our results allow us to describe the dispersion of metacentric B variants, in contrast with the elimination observed in acrocentric and submetacentric variants.
Keywords: Cytogenetics; migratory fish; Neotropical fishes; supernumerary chromosomes